Pengaruh Pendekatan Pendidikan Matematika Realistik Indonesia Terhadap Hasil Belajar FPB KPK Kelas IV SD - Safitri, Nurul Ulfa; Arlis, Syamsu (e-Jurnal Inovasi Pembelajaran Sekolah Dasar, 2022)
This research aims to find out the effect of Indonesia Realistic Mathematics Education approach on students’ learning outcome on the learning materials of GCD and LCM for fourth grade students in primary school Gugus I Kenagarian Tanjung Sani Maninjau. This reasarch uses quasi experiment design with non equivalent control design. The research samples are fourth grade students in primary school 17 Pandan and primary school 13 Tanjung Sani. From the data analysis using t-tes, the findings reveal that tobtained > ttable (2.97 > 1.684) on the level of α 0.05. Hence, it can concluded that Indonesia Realistic Mathematics Education approach has an effect on students’ learning outcome on the learning material of GCD and LCM for fourth grade students in primary school Gugus I Kenagarian Tanjung Sani Maninjau.